A new voice: translating medical questionnaires. (3rd May 2016) - Povoroznyuk, Roksolana; Dzerovych, Nataliia; Povoroznyuk, Vladyslav
Abstract : Medical translation is performed as a series of collaborative efforts from doctors and professional translators. Very often the results of their collaboration are medical questionnaires intended for patients. Medical survey instruments have proved their worth as reliable tools of a considerable predictive value, though their translation requires a specific methodology due to a culture-bound character of the material. Equivalence of the original and translated texts, translation quality, and the respondents' ultimate satisfaction with the surveying practice depend to a great extent upon the degree of translator's cultural competence, health literacy, and his/her awareness of the pragmatic and communicative aspects of translation. The task of producing and validating an accurate and fluently translated Ukrainian version of a disease-specific health-related quality-of-life instrument is exemplified by the IOF's 1-min risk test, a 10-item questionnaire, designed to evaluate the likelihood of developing osteoporosis.